Isolation and Analysis of Donor Chromosomal Genes Whose Deficiency Is Responsible for Accelerating Bacterial and Trans-Kingdom Conjugations by IncP1 T4SS Machinery - Zoolkefli, Fatin Iffah Rasyiqah Mohamad; Moriguchi, Kazuki; Cho, Yunjae; Kiyokawa, Kazuya; Yamamoto, Shinji; Suzuki, Katsunori (Frontiers in Microbiology, 2021)
Conjugal transfer is a major driving force of genetic exchange in eubacteria, and the system in IncP1-type broad-host-range plasmids transfers DNA even to eukaryotes and archaea in a process known as trans-kingdom conjugation (TKC). Although conjugation factors encoded on plasmids have been extensively analyzed, those on the donor chromosome have not. To identify the potential conjugation factor(s), a genome-wide survey on a comprehensive collection of Escherichia coli gene knockout mutants (Keio collection) as donors to Saccharomyces cerevisiae recipients was performed using a conjugal transfer system mediated by the type IV secretion system (T4SS) of the IncP1α plasmid. Out of 3,884 mutants, three mutants (ΔfrmR, ΔsufA, and ΔiscA) were isolated, which showed an increase by one order of magnitude in both E. coli–E. coli and E. coli–yeast conjugations without an increase in the mRNA accumulation level for the conjugation related genes examined. The double-knockout mutants for these genes (ΔfrmRΔsufA and ΔiscAΔfrmR) did not show synergistic effects on the conjugation efficiency, suggesting that these factors affect a common step in the conjugation machinery. The three mutants demonstrated increased conjugation efficiency in IncP1β-type but not in IncN- and IncW-type broad-host-range plasmid transfers, and the homologous gene knockout mutants against the three genes in Agrobacterium tumefaciens also showed increased TKC efficiency. These results suggest the existence of a specific regulatory system in IncP1 plasmids that enables the control of conjugation efficiency in different hosts, which could be utilized for the development of donor strains as gene introduction tools into bacteria, eukaryotes, and archaea.